2021
DOI: 10.47836/pjssh.29.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Work Value Orientation and TVET Students’ Career Decision-Making Self-Efficacy: The Mediating Role of Academic Major Satisfaction

Abstract: Graduates should know how technical and vocational education and training (TVET) can increase their employability and set them on a path to a professional career. However, graduate underemployment continues to be a severe and rising issue in many countries due to graduates’ lack of readiness to make a future career decision. The present study assessed the influence of work value orientation on Career Decision-Making Self-Efficacy (CDMSE) and the mediating role of Academic Major Satisfaction (AMS) on the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…This could indicate a positive relationship between academic learning environments, in which professional competence and self-efficacy are learned and applied, and clinical learning environments, in which there is some intrinsic and/or extrinsic factor that increases the acquisition of these nursing skills [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…This could indicate a positive relationship between academic learning environments, in which professional competence and self-efficacy are learned and applied, and clinical learning environments, in which there is some intrinsic and/or extrinsic factor that increases the acquisition of these nursing skills [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the study align with the sociocultural career theory in which this study is anchored and support those of previous research that showed that engaging in experiential/practice-based activities such as work-based learning, apprenticeship and internship programs has a strong positive probability on young people employability as it enhances their entrepreneurial self-efficacy and provides them with clear career direction (Kamaliah et al, 2018; Jackson, 2015). These experiential experiences, if integrated into the TVET curriculum, could stimulate learners' self-efficacy, particularly their perceptions, attitude and confidence, in tandem with the critical components of SCCT and consequently foster their capabilities of applying the knowledge and skills gained during the training in the world of work (Chen et al, 1998; Kamaruddin & Rasdi, 2021; Okolie et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The theory helps examine the role of learning experiences in skills development. It can also provide insights into how opportunities available within the TVET institutions environment in the context of Kenya could foster young people’s self-efficacy – their beliefs, attitude and confidence in possessing capabilities to engage in their career of choice (Bandura, 1997; Chen et al, 1998; Kamaruddin & Rasdi, 2021).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Their employment values are certainly rolled into the system, reflected by the increased importance of job stability and tendency of the system toward unit selection ( Liu and Zhang, 2021 ). Employment values have a significant impact on college students’ employment quality ( Zhong and Liu, 2015 ), employment anxiety ( Wang et al, 2014 ), initial employment results ( Yin and Fan, 2015 ), job satisfaction and career development ( Yarbrough et al, 2016 ), career decision-making self-efficacy ( Doo and Park, 2019 ; Kamaruddin and Rasdi, 2021 ), and so on. Currently, numerous employment values of college students are characterized by subjectivity and realism, and their employment expectations are high, resulting in reduced employment satisfaction.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%